2019
DOI: 10.1002/cam4.2541
|View full text |Cite
|
Sign up to set email alerts
|

Fecal occult blood test screening uptake among immigrants from Muslim majority countries: A retrospective cohort study in Ontario, Canada

Abstract: BackgroundColorectal cancer (CRC) is the second and third highest cause of cancer deaths among Canadian men and women, respectively. Population‐based screening through fecal occult blood testing (FOBT) has been proven to be effective in reducing CRC morbidity and mortality. Although participation in Ontario's organized CRC screening program has been increasing steadily since 2008, its uptake remains low among recent immigrant populations despite the known benefits of screening. To promote participation in CRC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…One study from Chicago, which included a significant number of African American Muslim women along with Arab American and South Asian American Muslim women, did not confirm the effect of modesty concerns on cervical cancer screening, perhaps because it examined both recent immigrants and Muslims who had resided in the area for longer periods of time. [67] Interestingly, all of the included studies found that a relationship with a primary care provider resulted in improved screening rates [65] , [66] , [67] , [68] , [69] , [70] , [71] , which supports the role of primary care in cancer screening. The challenges and barriers mentioned previously may be more prevalent for Muslim women.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…One study from Chicago, which included a significant number of African American Muslim women along with Arab American and South Asian American Muslim women, did not confirm the effect of modesty concerns on cervical cancer screening, perhaps because it examined both recent immigrants and Muslims who had resided in the area for longer periods of time. [67] Interestingly, all of the included studies found that a relationship with a primary care provider resulted in improved screening rates [65] , [66] , [67] , [68] , [69] , [70] , [71] , which supports the role of primary care in cancer screening. The challenges and barriers mentioned previously may be more prevalent for Muslim women.…”
Section: Resultsmentioning
confidence: 73%
“…One of the aims of primary care is to prevent disease or to detect disease before it negatively affects patients’ health. The benefit of screening is highly dependent on the proportion of the population participating in testing, and lack of understanding and accommodation of Islamic religious requirements may increase reluctance to utilize healthcare [64] and negatively impact preventive care such as colorectal [65] , cervical [66] , [67] , and breast cancer [68] screening rates, contributing to delayed diagnosis and inequitable outcomes. However, this evidence is limited by most of studies being performed in recent Muslim immigrants and may not be generalizable to the greater Muslim community.…”
Section: Resultsmentioning
confidence: 99%
“…18 There were three exposure groups defined as (1) Muslim majority country (>50% identify as Muslim), (2) moderate proportion Muslim country (≥10% to ≤50% identify as Muslim) and (3) Muslim minority country (<10% identify as Muslim). Similar assignment of each country to a Muslim proportion has been used in other studies, as individual-level measures of religion are not measured or available across the population 19 21 and groupings were congruent with proportions identifying as Muslim from the United Nations Demography Yearbook. 22…”
Section: Methodsmentioning
confidence: 92%
“…18 There were three exposure groups defined as (1) Muslim majority country (>50% identify as Muslim), (2) moderate proportion Muslim country (≥10% to ≤50% identify as Muslim) and (3) Muslim minority country (<10% identify as Muslim). Similar assignment of each country to a Muslim proportion has been used in other studies, as individual-level measures of religion are not measured or available across the population [19][20][21] and groupings were congruent with proportions identifying as Muslim from the United Nations Demography Yearbook. 22 A secondary exposure was generation status with firstgeneration immigrants not born in Canada and arriving after their birth date, and second-generation immigrants born in an Ontario hospital with a mother with an IRCC immigration record from or after 1985.…”
Section: Exposuresmentioning
confidence: 94%
“…Equivalent data are not available for Canadian comparisons or to inform policy. However, many studies of health disparities in cancer screening in Canada show that new immigrants have significantly lower cancer screening rates, which contributes to disparities in cancer treatment outcomes 83–95. Groups such as Indigenous people and recent immigrants have more than one risk factor related to SDOH, increasing their likelihood of poorer health outcomes 96.…”
Section: Introductionmentioning
confidence: 99%